A Review on Repurposing of Drug - Aqsa Jannat, Sadia Rafique, Sana Javed, Aamna Habib, Zunaira Afzal (Pakistan Journal of Medical & Health Sciences, 2024)
Background: For discovering novel drugs and to gain market acceptance process of conventional drug discovery is used in which various stages are involved. Aim: To innovate new approaches for minimizing the cost and time of drug discovery. Method: Several attempts were made for the building of plans based on computational tools and on bio-informatics to strengthen the repurposing method off-late. Various approaches used to invent novel signs for FDA accepted drugs are discussed in this review. Results: The repurposing of the drugs has obtained significance in identifying novel therapeutic uses for existing drugs. It is a productive strategy for the discovery of drugs also time and cost-effective.It fills the gap for the absence of efficiency of conventional drug development. Implications: In drug repurposing, selection and decision of suitable repurposing technique depend on previous knowledge and accessible data from particular studies. The best advantage of the drug repurposing technique is that for approved drugs all the required data is available. Conclusion: This technique is currently appearing to overcome the restriction faced during conventional drug discovery in the form of resources, timeline, and financial support . The feasibility of repurposing technique is improved by its systematic application. Some examples of repurposed drugs are also reviewed here. This review also covers the skill of repurposing survival drugs for use against microbes. Keywords: Conventional drug, drug repurposing, repurposing approaches, docking, proteinopathy.